Effect of buoyant torque on body roll of unilateral arm amputee front crawl swimmers - Payton, C. J.; Osborough, C.; Sanders, R. H. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Rotation about the body`s longitudinal axis in front crawl swimming or `bodyroll` may serve many useful functions including: facilitating the breathing action, aiding arm recovery and reducing drag. The torque exerted by the buoyant force about the longitudinal axis, as the arm is recovered over the water, is an important mechanism for driving bodyroll. A single arm amputation may limit a swimmer`s ability to generate bodyroll. The purpose of this study was to quantify the buoyant torque experienced by single arm amputee front crawl swimmers about their longitudinal axis and its effect on their bodyroll. METHODS: The buoyant torque acting about the longitudinal axis depends on the positions of the whole body centre of mass (CM) and centre of buoyancy (CB) relative to this axis, and the magnitude of the buoyant force. These variables were calculated from body segment masses and volumes, and the position-time histories of each segment. Six female single arm (at-elbow) amputees performed nonbreathing front crawl trials at sprint pace. Trials were recorded above and below water with six video cameras. A thirteen-segment full body model of the swimmer was defined. One complete stroke cycle was digitised and 3D coordinates obtained. Body segment data were calculated from digital photographs of the participants, using the elliptical zone method. Bodyroll was described by the angular displacements of the upper trunk (shoulder roll) and lower trunk (hip roll). Buoyant torque was obtained from the cross product of the whole body CM— CB position vector and the buoyant force vector. RESULTS: Swimmers experienced significantly higher peak buoyant torques during recovery of the unaffected arm (8.1±1.4 N.m) than during recovery of the partially-amputated arm (3.5±0.9 N.m). Maximum body roll angles during the unaffected-arm recovery (shoulder: 41±8°; hip: 30±5°) were higher than those during recovery of the partially amputated arm (shoulder: 32±6°; hip: 23±6°). DISCUSSION: The buoyant torque always acted to decelerate the bodyroll from arm exit to mid-recovery and then to accelerate it from mid-recovery to arm entry. The considerable bilateral asymmetry in the buoyant torque could not account for the bodyroll patterns displayed by any of the swimmers. This indicates that the swimmers were utilising mechanisms other than the buoyant torque, such as external torques from non-propulsive fluid forces, to control their bodyroll.